2017
DOI: 10.1001/jamacardio.2016.5501
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Patients With Stable Chest Pain Deriving Minimal Value From Noninvasive Testing

Abstract: clinicaltrials.gov Identifier: NCT01174550.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 22 publications
(26 reference statements)
3
57
1
10
Order By: Relevance
“…In both trials, the use of a symptom-focused strategy endorsed by NICE, in contrast with a Bayesian–risk based approach endorsed by ACC/AHA and ESC, resulted in a 3- to 4-fold increase in the number of patients for whom no further investigation for the presence of CAD is recommended. This is reassuring given concerns raised recently that the updated NICE guidance would lead to an increase in indiscriminate diagnostic testing (19) , as well as strategies being considered to defer testing in those patients with very low risk 20 , 21 . Furthermore, the group designated by NICE for no testing (nonanginal symptoms) demonstrated <10% prevalence of coronary obstruction across both trial cohorts, below the threshold adjudged to reflect low risk in both the ACC/AHA and ESC guidelines.…”
Section: Discussionmentioning
confidence: 90%
“…In both trials, the use of a symptom-focused strategy endorsed by NICE, in contrast with a Bayesian–risk based approach endorsed by ACC/AHA and ESC, resulted in a 3- to 4-fold increase in the number of patients for whom no further investigation for the presence of CAD is recommended. This is reassuring given concerns raised recently that the updated NICE guidance would lead to an increase in indiscriminate diagnostic testing (19) , as well as strategies being considered to defer testing in those patients with very low risk 20 , 21 . Furthermore, the group designated by NICE for no testing (nonanginal symptoms) demonstrated <10% prevalence of coronary obstruction across both trial cohorts, below the threshold adjudged to reflect low risk in both the ACC/AHA and ESC guidelines.…”
Section: Discussionmentioning
confidence: 90%
“…The newly developed PROMISE (Prospective Multicenter Imaging Study of Chest Pain) minimal risk tool was designed to identify “low‐risk” patients in whom deferred noninvasive testing (noninvasive coronary angiography or functional stress testing) may be considered 56. Subjects with minimal risk had a low‐risk profile (0.5% risk of cardiovascular death and MI at a median 25 months).…”
Section: Obstructive Cad Likelihood Scoresmentioning
confidence: 99%
“…Comparison of primary, secondary prevention risk versus observed risk in an example of stable INOCA patient is presented in Figure 2 40, 47, 56, 63, 65, 66, 67, 68, 69, 70, 71. The primary prevention scores, developed in asymptomatic populations, predicted that risks vary between 1% and ≈5% and underestimate the observed INOCA risk.…”
Section: Primary and Secondary Prevention Risk Versus Observed Inoca mentioning
confidence: 99%
“… 39 We have also reported that absence of hypertension, dyslipidaemia and tobacco use are associated with a lower rate of adverse cardiovascular events. 40 We also found that treatment gaps among patients with hypertension or diabetes were not associated with an increased risk of adverse cardiovascular events. In contrast, treatment gaps among patients with dyslipidaemia were associated with an increased risk of adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 59%